Avaliação da influência de parâmetros geométricos no recalque de sapatas próximas a escavações utilizando análise estatística: um estudo de caso em Alegrete-RS - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This study aimed to evaluate the influence of geometric parameters on the settlement of shallow foundations located near excavations, through numerical modeling and statistical analysis. For this purpose, simulations were carried out using the Rocscience RS2 software, representing a strip footing subjected to a constant stress of 300 kPa, representative of the typical soil condition in the city of Alegrete-RS, BrazilOne of the geometric parameters of the model, the maximum excavation depth, was limited to 4 meters, based on typical conditions observed in the city of Alegrete, Brazil. A total of 27 simulations were conducted, varying the footing width, excavation depth, and the distance between the footing and the excavation. Based on the results obtained, it was possible to quantify the settlements generated in each scenario and apply statistical methods. The analysis of variance (ANOVA), performed using the Statistica software, allowed for the identification of the parameters that exerted the greatest influence on the observed settlement. Linear regression, also conducted in the same software, enabled the development of an empirical equation to estimate settlement, with an error margin consistent with the simulated data. In addition to the isolated effects of each variable, combinations between the geometric parameters were also analyzed, aiming to understand interactions that intensify settlement effects. The results indicate that small variations in geometric parameters can significantly affect foundation performance, especially in scenarios involving nearby excavations. Furthermore, the statistical analysis made it possible to identify the parameter with the greatest influence on settlement, providing a solid basis for more accurate foundation design decisions. The study highlights the importance of considering these geometric interactions during the design phase and demonstrates that the combination of numerical modeling and statistical analysis is a powerful tool in supporting geotechnical engineering, contributing to safer and more efficient solutions in urban environments.
Keywords: Engenharia civil; Fundações; Recalque de estruturas; Estatística - Análise; Parâmetros geométricos; Civil engineering; Fundations; Structural settlement; Statistics - analysis; Geometric parameters; ENGENHARIAS